Principles of protection of personal data: сomparative analysis of national and foreign legislation (Journal of actual problems of jurisprudence, 2023)
Information and communication technologies have become integral to modern life, providing access to information, goods, and services. Modern technologies make it possible to collect a wide range of data and information about a person, linking all his documents and data to his account and profile, tracking his actions, getting an idea of ​​a person’s habits and preferences, and using the information received for various purposes. The Republic of Kazakhstan occupies one of the top places in the world in the implementation and use of digital technologies in the public and political life of the country.This article discusses the principles of personal data protection enshrined in the national law. The object of the study is public relations related to privacy, in particular, the protection of personal data in the Republic of Kazakhstan. The research subject is the legislation on protecting personal data, as well as some issues of law implementation practice.The purpose of the study is to identify the problematic aspects of the institution of personal data protection in the Republic of Kazakhstan and, on this basis, to argue proposals and recommendations for the current legislation. The authors used general scientific and private research methods to prepare the study. A comparative analysis, mainly external and regulatory comparisons, has been conducted. The authors analyzed legal norms, articles of normative legal acts of some states, and normative definitions of the compared laws to identify differences. Legislative consolidation of provisions like the principles in the Kazakh law was found at the level of obligations of owners and operators of databases rather than at a more significant level of regulatory principles. Possible risks of using personal information by unscrupulous persons to the detriment of a person, his interests and property are identified. The conclusion is made about the need for regulatory consolidation of the principles of personal data protection following internationally recognized standards at a level of normative principles.Key words: human rights and freedoms, privacy, protection of personal data, principles of law, confidentiality.